Influence of third opinion leaders on decision making quality: A case on financial decision making - Nik Maheran Nik Muhammad; Rikinorhakis Ridzwan (Mediterranean Center of Social and Educational Research, 2015)
Many top leaders nowadays are relying on external parties to get ideas and information for more effective and quality decision-making. For certain leaders, the power of thinking partners is the factor of success in their decision making process. This study therefore aimed to identify the influence of third opinion leaders in enhancing the relationship between leadership styles and financial decision-making quality. Based on the initial work of Joni (2004 ) and Path-Goal theory, with 211 usable respondents using hierarchical regression analysis, shows that the quality of financial decision is significant and positively related to leadership behavior. Third opinion’s mind and third opinion’s relationship act as pure moderator, while third opinion’s focus was found to be a quasi-moderator. For theoretical implication, the findings suggest that the inclusion of the moderating variable will further enhance the understanding of the differential impact of leadership style under various contexts of decision-making situation, in this case, the third opinion. For future research, it is recommended that differences relation to leadership behavior should be studied more extensively to reach various kinds of comparative conclusions.